MANAJEMEN KURIKULUM PROGRAM UNGGULAN TAHFIZUL QURAN DALAM MENCAPAI TARGET ONE YEAR ONE JUZ DI SD ISLAM QURANI TEMANGGUNG - Lutvia rizki andini (Elementary School and Education Journal, 2025)
This research aims to analyze the curriculum management of the Tahfizul Quran program in achieving the One Year One Juz target at SD Islam Qurani Temanggung. The research used a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The data analysis technique employed Miles and Huberman's interactive model, including data reduction, data display, and conclusion drawing. The results indicate that curriculum planning involves the principal, tahfiz coordinator, teachers, the foundation, and Jam’iyyah Qurro’ Wal Huffaz NU Temanggung. The organization stage includes task delegation and scheduling. The program is implemented daily with activities such as ziyadah (new memorization), murojaah (review), tahsin (recitation improvement), and kitabatul Quran (Quran writing). Evaluation is carried out monthly and involves both teachers and parents. Several challenges were identified in achieving the One Year One Juz target, including limited number of tahfiz teachers, large class sizes, low student motivation, unstable emotional conditions, and lack of parental support. The study suggests the need for adaptive and collaborative curriculum planning to improve the effectiveness of the tahfiz program.